肝活检确诊药物性肝损害的病因及临床特征分析 - Li-tong, XU; CHEN, Shong-hai; Zhong-bin, LI; LI, Zhi; He-bin, FAN; TAO, Ying; Guo-feng, CHEN; JI, Dong (Jie fang jun yi xue za zhi, 2018)
Objective To investigate the etiology and clinical features of drug-induced liver injury (DILI). Methods A total of 194 DILI in patients, who underwent liver biopsy in our hospital from January 2015 to December 2015, were enrolled in the study. The etiology, laboratory markers (such as alanine transaminase, aspartate aminotransferase, total bilirubin, gamma- glutamyl transferase and alkaline phosphatase), and the pathological features were analyzed retrospectively. Then, all of the patients were followed up every 3 or 6 months, with a mean of 34.5 months. The risk factors associated with relapse, which was defined as liver enzymes ( such as ALT or TBIL) rising at least 2 times of its upper limit of normal value (ULN), were analyzed with a logistic regression model. Results In terms of etiology, Traditional Chinese medicine (TCM) was the most common cause of DILI, which accounted for 46.9% of patients, in return followed by acetaminophen-containing drugs (14.4%), antibiotics (9.3%), environmental toxins (4.6%)